2020
DOI: 10.20471/acc.2020.59.s1.16
|View full text |Cite
|
Sign up to set email alerts
|

Skip Metastases in Papillary Thyroid Carcinoma – Prevalence, Predictive and Clinicopathological Factors

Abstract: SUMMARY Background Cervical lymph node metastases are frequently found in papillary thyroid carcinoma (PTC) and occur in a stepwise fashion. Skip metastases that omit the central compartment and spread initially in lateral neck levels are present in a certain share of patients, and their significance is poorly understood. The aim of this prospective study was to identify their possible predictors and clinicopathological factors in a group of patients with PTC with lateral lymph node (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Skip metastasis occurs when tumor cells bypass the CLNs, and metastasis first occurs in the LLNs. This phenomenon has been reported in several studies, affecting approximately 21.8–23.5% of patients [ 6 , 7 ]. In this study, 13 of 203 patients with lateral metastasis had skip metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…Skip metastasis occurs when tumor cells bypass the CLNs, and metastasis first occurs in the LLNs. This phenomenon has been reported in several studies, affecting approximately 21.8–23.5% of patients [ 6 , 7 ]. In this study, 13 of 203 patients with lateral metastasis had skip metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…It is generally accepted that tumor cells spread in a stepwise way: from central to lateral neck regions. Skip metastases that omit the central compartment and spread initially in lateral neck levels only occur in a small number of patients ( 8 ). In addition, researchers confirmed that large-volume CCLNM was an independent risk factor of lateral LNM in PTC ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rate of clinical lateral metastasis in patients was 10%, and in the literature, the prevalence of LLNM in patients with PTC ranged from 6.5% to 27.5%. [ 5 , 6 ] In the literature, the male sex ratio is reported to be higher in patients with LLNM. [ 6 ] In a comprehensive meta-analysis, including 18741 patients of 23 studies, by So et al, [ 23 ] male gender is found to be an effective factor in the development of LLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion is considered another risk factor for the development of LLNM. [ 5 ] In the study of Lombardi et al, [ 31 ] the number of skip lateral metastases without metastases in the central compartments was reported to be significantly higher in patients with lymphovascular invasion. In another meta-analysis including 23 studies and 18741 patients evaluating LLNM in PTC; lymphovascular invasion was determined as a significant risk factor for the development of LLNM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation